The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0004-282x2003000200017
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin for treatment of Frey's syndrome: report of two cases

Abstract: Frey's syndrome is a phenomenon of hemifacial flushing and sweating after gustatory stimulus, usually secondary to surgical trauma over the parotid gland, although other injury mechanisms may be seen. It is accepted as a result of aberrant regeneration of facial autonomic nerve fibers. Treatment evolved from ineffective medical and surgical approaches to botulinum toxin. We evaluate the effectiveness and safety of botulinum toxin in the treatment of this complication in two patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Consequently, gustatory stimulus will cause sweating of the skin in the pre-auricular area. [714] Many therapeutic approaches have been tried for managing Frey's syndrome including medical and surgical procedures. While medical therapies like systemic anti-cholinergics are not well-tolerated, surgical procedures seem disproportionate to symptomatology and ineffective.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, gustatory stimulus will cause sweating of the skin in the pre-auricular area. [714] Many therapeutic approaches have been tried for managing Frey's syndrome including medical and surgical procedures. While medical therapies like systemic anti-cholinergics are not well-tolerated, surgical procedures seem disproportionate to symptomatology and ineffective.…”
Section: Applicationsmentioning
confidence: 99%
“…Pornprasit M injected 2 unit or 0.1 ml intradermal BT type A at every 1 cm 2 affected area determined using starch-iodine test as a diagnostic criterion. [914] The author noted significant improvement in the symptoms and concluded that intradermal injection of botulinum toxin type A for patients with Frey's syndrome is not only effective with no side-effect but also minimally invasive. After toxin injection, duration of symptom-free periods is variable.…”
Section: Applicationsmentioning
confidence: 99%
“…The majority of patients postparotidectomy will have a positive starch–iodine test, but not all are symptomatic. Severe symptoms occur in about 15% . Surgical treatments for Frey syndrome, either as prophylaxis at the time of parotidectomy or subsequently to block nerve conduction mechanically, have also been reported .…”
Section: Summary Of Cases Including Patient Characteristics Site Anmentioning
confidence: 99%
“…Surgical treatments for Frey syndrome, either as prophylaxis at the time of parotidectomy or subsequently to block nerve conduction mechanically, have also been reported . Treatment of Frey syndrome with botulinum toxin has been described in a number of case reports and series, using varying amounts of botulinum toxin, with relief from symptoms for several months …”
Section: Summary Of Cases Including Patient Characteristics Site Anmentioning
confidence: 99%
“…1 It frequently presents with moderate manifestations, however, several patients may experience severe discomfort accompanied by a significant social burden; 2 male to female ratio is estimated to be 1:1. 3,4 The syndrome was initially described by Duphenix 5 in 1757, and later by Baillarger 6 in 1853. However, it was named after Lucja Frey, a Polish neurologist, who published in 1923 the case of a 25-year-old patient suffering from facial sweating and local skin flushing during meals, as a consequence of a gunshot wound that affected his parotid gland.…”
Section: Introductionmentioning
confidence: 99%